The American Society of Peritoneal Surface Malignancies evaluation of HIPEC with Mitomycin C versus Oxaliplatin in 539 patients with colon cancer undergoing a complete cytoreductive surgery. Issue 7 (2nd August 2014) - Prada‐Villaverde, Arancha; Esquivel, Jesus; Lowy, Andrew M.; Markman, Maurie; Chua, Terence; Pelz, Joerg; Baratti, Dario; Baumgartner, Joel M.; Berri, Richard; Bretcha‐Boix, Pedro; Deraco, Marcello; Flores‐Ayala, Guillermo; et al.
Abstract Background Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) are gaining acceptance as treatment for selected patients with colorectal cancer with peritoneal carcinomatosis (CRCPC). Tremendous variations exist in the HIPEC delivery. Methods The American Society of Peritoneal Surface Malignancies (ASPSM) examined the overall survival in patients with CRCPC who underwent a complete cytoreduction and HIPEC with Oxaliplatin vs. Mitomycin C (MMC), stratifying them by the Peritoneal Surface Disease Severity Score (PSDSS). Results Median overall survival (OS) of 539 patients with complete cytoreduction was 32.6 months, 32.7 months for the MMC group and 31.4 months for the Oxaliplatin group (P = 0.925). However, when stratified by PSDSS, median OS rates in PSDSS I/II patients were 54.3 months in those receiving MMC vs. 28.2 months in those receiving oxaliplatin (P = 0.012), whereas in PSDSS III/IV patients, median OS rates were 19.4 months in those receiving MMC vs. 30.4 months in those receiving Oxaliplatin (P = 0.427). Conclusion These data suggest that MMC might be a better agent for HIPEC delivery than Oxaliplatin in patients with CRCPC, favorable histologies and low burden of disease (PSDSS I/II) undergoing complete cytoreduction. Propsective studies are warranted, which stratify patients by their PSDSS and randomize them to HIPEC with MMC vs. Oxaliplatin. J. Surg. Oncol. 2014 110:779–785. © 2014 Wiley Periodicals, Inc.